The role of corticosteroids in the management of chronic subdural hematoma: a systematic review - Lotte M.E. Berghauser Pont; Clemens M.F. Dirven; Diederik W.J. Dippel; Bon H. Verweij; Rúben Dammers (2012)
The role of corticosteroids in the management of chronic subdural hematoma (CSDH) remains a matter of debate. Standard surgical treatment has recurrence rates reported between 4 and 26%. We reviewed the safety and effectiveness of corticosteroids both as a monotherapy and as an adjunct to surgery in patients with CSDH. PubMed-MEDLINE, EMBASE and Cochrane databases were searched in July 2011 for randomized controlled trials and for prospective and retrospective cohort studies, reporting on 10 or more adult patients with CSDH. Quality was assessed according to the STROBE checklist. Corticosteroid monotherapy and surgery with corticosteroids as an adjunct were compared with no treatment or surgery only, with regard to lethality, neurological outcome, secondary intervention and complications. Five observational studies were included in this review. There was no randomized allocation of treatment in any study. Secondary intervention rates ranged from 3 to 28%, lethality rates ranged from 0 to 13%, and good outcome was seen in 83-100%. Hyperglycemia occurred more often in patients treated with corticosteroids. In only two studies, one case of gastrointestinal bleeding was observed. Five observational studies suggest that corticosteroids might be beneficial in the treatment of CSDH; however, there is a lack of well-designed trials that support or refute the use of corticosteroids in CSDH. These results encourage further randomized clinical trials to establish the role of corticosteroids in CSDH.